Effectiveness Of Coping Strategies On Student Academic Anxiety Based On Empirical Study-Based Systematic Review - Alpiah, Dini Nur; Puring, Raihan; Dinata, Cakra; Herawan, Herawan; Wijaya, Krisna (Ridwan Institute, 2025)
This study aims to conduct a systematic review related to academic anxiety management strategies in students, especially relevant to the field of physiotherapy in the context of Communication Psychology and Psychosomatic Disorders courses. Literature searches were conducted on PubMed, Scopus, and Google Scholar databases for the period 2015–2025. Inclusion criteria include empirical research articles that evaluate the effectiveness of intervention strategies (psychological and non-psychological) on students' academic anxiety, with a population of at least 50% of students of the health study program. Of the 1,247 articles identified, 28 met the inclusion criteria. The results of the review showed several groups of effective strategies, including a cognitive-behavioral approach (Cognitive Behavioral Therapy (CBT) with psychoeducation and skills training programs, Mindfulness-Based Stress Reduction (MBSR)-based interventions, relaxation and diaphragmatic breathing techniques, time management and workload management training, and social support through peer mentoring groups. In particular, studies in physiotherapy students emphasized the need for integrated support programs that focus on recognizing signs of somatic stress (e.g. headaches, muscle tension) and providing effective communication guidance between lecturers and students to reduce anxiety. These findings are expected to be the basis for the development of guidelines for academic anxiety management strategies that meet the needs of the physiotherapy study program.